AC ionic conductivity and DC polarization method of lithium ion transport in PMMA–LiBF4 gel polymer electrolytes - Z. Osman; M.I. Mohd Ghazali; L. Othman; K.B. Md Isa (ScienceDirect, 2024)
Non-Indexed Publication